2020
DOI: 10.3390/ijms21145096
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Metabolic Reactions of Semi-Dwarf, Barley Brassinosteroid Mutants to Drought

Abstract: The roles of endogenous brassinosteroids (BRs) in the modulation of reaction to drought and genetic regulation of this process are still obscure. In this study, a multidirectional analysis was performed on semi-dwarf barley (Hordeum vulgare) Near-Isogenic Lines (NILs) and the reference cultivar “Bowman” to get insights into various aspects of metabolic reaction to drought. The NILs are defective in BR biosynthesis or signaling and displayed an enhanced tolerance to drought. The BR metabolism perturbations affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…In the case of the semi-dwarf, erect line BW312 which along with other BR-related semi-dwarf NILs showed improved tolerance to drought in our previous studies [16,18], and in this study displayed the highest values of the productive tillering and the average grain weight per plant (under the drought conditions), there may be an additional opportunity for yield increase through higher planting density and improved drought tolerance. Therefore, the BW312 line, which represents the new allele of the HvBRI1 (Uzu1) gene-uzu1.b, may constitute an alternative in future barley breeding programs, taking into account the ongoing climate change and necessity of developing new drought-tolerant crop cultivars.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the case of the semi-dwarf, erect line BW312 which along with other BR-related semi-dwarf NILs showed improved tolerance to drought in our previous studies [16,18], and in this study displayed the highest values of the productive tillering and the average grain weight per plant (under the drought conditions), there may be an additional opportunity for yield increase through higher planting density and improved drought tolerance. Therefore, the BW312 line, which represents the new allele of the HvBRI1 (Uzu1) gene-uzu1.b, may constitute an alternative in future barley breeding programs, taking into account the ongoing climate change and necessity of developing new drought-tolerant crop cultivars.…”
Section: Discussionsupporting
confidence: 59%
“…It was postulated that modifications of plant architecture by manipulating the BR biosynthesis or signaling may be a feasible approach for improving crop yield [12]. Importantly, recent reports in the dicot and monocot model species Arabidopsis thaliana (thale cress) and Brachypodium distachyon (purple false brome), as well as in the important crops Oryza sativa (rice) and Hordeum vulgare (barley) indicated that mutants defective in the BR metabolism show a various degree of plant height reduction and an enhanced tolerance to drought [13][14][15][16][17][18]. It is known that cereal crops adapt to drought by decreasing their leaf size and delaying flowering [19].…”
Section: Introductionmentioning
confidence: 99%
“…The samples were analyzed in triplicates. POD activity 54 , CAT activity 54 , SS content 55 , IAA content 56 , SP and MDA content 57 were analyzed as indicators of physiological response. The majuscules indicated a significant difference (p < 0.05) for the freezing stress-treated samples compared with chilling stressed samples.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were performed three times with similar results. POD activity [51], CAT activity [52], SS content [53], IAA content [54], SP and MDA content [55] were analyzed as indicators of physiological response. The majuscules indicated a significant difference (p < 0.01) for the freezing stress-treated samples compared with chilling stressed samples.…”
Section: Methodsmentioning
confidence: 99%